2020
DOI: 10.1111/jzs.12375
|View full text |Cite
|
Sign up to set email alerts
|

Multiple refugia and glacial expansions in the Tucumane–Bolivian Yungas: The phylogeography and potential distribution modeling ofCalomys fecundus(Thomas, 1926) (Rodentia: Cricetidae)

Abstract: The Yungas, a subtropical mountain rainforest of South America, has been little studied in relation to the evolutionary history of the large‐bodied species of the genus Calomys. Particularly, two species have been synonymized: C. boliviae and C. fecundus; the first is only known from its type locality in the northern Bolivian Yungas, whereas the second is known along the Tucumane–Bolivian Yungas shared by Bolivia and Argentina. In this study, we combined a phylogeographic approach with ecological niche modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 54 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…At chromosome level, specimens of C. fecundus from Famaillá in Tucumán Province present a 2 n = 54 (FN = 66; Hurtado de Catalfo & Wainberg, 1974), being the same 2 n reported for animals from Tarija and Chuquisaca in southern Bolivia (Salazar‐Bravo et al, 2002). These data agree with phylogeographic results presented by Pinotti et al (2020) and ours, where genetic continuity is found throughout the distribution range of the species. In relation to health issues, C. fecundus is a reservoir of the Laguna Negra orthohantavirus that causes the hantavirus pulmonary syndrome (Pini et al, 2012) and is also a reservoir of a Latino‐like mammarenavirus (apparently non‐pathogenic; Calderón et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…At chromosome level, specimens of C. fecundus from Famaillá in Tucumán Province present a 2 n = 54 (FN = 66; Hurtado de Catalfo & Wainberg, 1974), being the same 2 n reported for animals from Tarija and Chuquisaca in southern Bolivia (Salazar‐Bravo et al, 2002). These data agree with phylogeographic results presented by Pinotti et al (2020) and ours, where genetic continuity is found throughout the distribution range of the species. In relation to health issues, C. fecundus is a reservoir of the Laguna Negra orthohantavirus that causes the hantavirus pulmonary syndrome (Pini et al, 2012) and is also a reservoir of a Latino‐like mammarenavirus (apparently non‐pathogenic; Calderón et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…However, these two entities should be considered different species, because in addition to Thomas original diagnostic traits, Olds (1988) noted that adult females of C. boliviae had five pairs of mammae, while those of C. fecundus had seven pairs. From a different point of view, Pinotti et al (2020), using ecological niche modelling, showed that none of the potential distribution models predicted the presence of C. fecundus in the type locality of C. boliviae . Therefore, the authors proposed that C. fecundus would be restricted to the Tucumane–Bolivian Yungas and C. boliviae to the northern Bolivian Yungas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the former, Salazar Bravo et al (2001) based on molecular analysis of mitochondrial genes, suggested that the name C. fecundus should be applied to the Yungas populations of NWA and Bolivia, but then, without further evidence, he listed C. fecundus as a junior synonymous of C. boliviae in a recent checklist of South American Mammals [22]. Furthermore, Pinotti et al, (2020) based on molecular and potential distribution approaches suggest that the Bolivian Montane Dry Forest could have acted as a barrier for the differentiation between C. boliviae and C. fecundus. Thus, we included in our searches keywords O. f. occidentalis (the name applied by some authors for the western clade of O. avescens) and C. fecundus (the name applied to southern populations of C. boliviae).…”
Section: Dataset Of Rodent Species Presencementioning
confidence: 99%